PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PUSAT KOPERASI PEGAWAI RI (PKPRI) KOTA BANDUNG - Ahmad Husen (Cross-border, 2022)
This research is motivated by the idea of the importance of the performance of cooperative employees, especially at the Indonesian Civil Servant Cooperative Center (PKPRI) Bandung City, which is of quality and in accordance with company standards so that company goals can be achieved, considering that in essence employees are the main wealth of a company which is required to play an active role in establishing plans, systems, processes and company goals to be achieved. Factors that influence employee performance include compensation and employee work discipline. The purpose of this study is to uncover, know, study and analyze the magnitude of the effect of compensation and work discipline on employee performance so that researchers formulate this research problem with five research questions; 1) What is the relationship between compensation and work discipline, 2) How does the effect of compensation on employee performance, 3) How does the influence of work discipline on employee performance, 4) How do the effects of compensation and work discipline jointly on employee performance, 5) What are the steps taken to improve and improve the performance of PKPRI Bandung City employees. Supported by an appropriate theoretical study, this study used a descriptive method and a quantitative approach to the population at PKPRI Bandung city, by using a questionnaire as a data collection medium and processed with a systematic step of testing relationships and influences, this study resulted in the following conclusions; 1) Compensation has a low relationship with Work Discipline. 2) Compensation has a very low effect on employee performance. 3) Work Discipline has a strong influence on Employee Performance. 4) Compensation and work discipline together have a strong influence on performance. The implication of the results of this study is to improve employee performance by increasing compensation and work discipline, because both are proven to have a positive influence.